Defeating degradation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Working with farmers for better land husbandry edited by Norman Hudson and Rodney Cheatle 1993 272pp ISBN 1 85339 122 0 Pbk pace UKL9.95 IT Publications 103-105 Southampton Row London WC1B 4HH, UK